A sodium ion battery positive electrode material, a preparation method thereof and a sodium ion battery
By co-doping metal elements and sulfur elements, the problem of the problem that the cathode material of sodium ion battery is difficult to improve capacity and stability without increasing the upper voltage limit, achieving higher capacity, cycle stability and rate performance, and improving the air stability and processing performance of the material.
Patent Information
- Application Number
- CN202210628529.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-06-06
AI Technical Summary
The existing sodium ion battery positive electrode materials are difficult to improve capacity, cycle stability and rate performance at the same time without increasing the upper voltage limit, and there are problems with electrolyte decomposition and metal dissolution.
By co-doping with doped metal elements and sulfur elements, a wider Na+ migration channel is built to regulate the capacity of the layered positive electrode material within a specific voltage range, and to improve the first-week charging capacity and stabilize the lattice oxygen through the recombination of sulfides and residual alkalis.
It is achieved to improve the capacity, cycle stability and rate performance of the positive electrode material of sodium ion battery without increasing the upper voltage limit, and improve the air stability and processing performance of the material.
Smart Images

Figure CN115207352B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a sodium ion battery positive electrode material, a preparation method thereof, and a sodium ion battery. Background Art
[0002] In the current situation of energy shortage, it is particularly important to develop new energy storage batteries such as lithium-ion batteries and sodium-ion batteries in a healthy and orderly manner, accompanied by the country's increasing requirements for the energy density of power batteries and the urgent hope that sodium-ion batteries will enter the market earlier to alleviate energy storage pressure. At present, the energy density of sodium-ion batteries is relatively low. Although layered oxide positive electrode materials have a high theoretical capacity, increasing the charging cut-off voltage will bring about problems such as metal dissolution and electrolyte decomposition. Therefore, it is necessary to study methods that can exert more capacity, effectively inhibit electrolyte decomposition, and reduce metal dissolution within the existing voltage range.
[0003] Existing doping modification is mostly different types of metal ion doping and halogen anion doping or co-doping, and mainly fluorine doping, which has problems such as large equipment loss and environmental pollution. In addition, ion doping can only solve the problem of material structure stability, but the interface problem still exists, and coating modification is required, which leads to an increase in process steps, cumbersome operation, and additional cost.
[0004] CN 112242510A discloses a preparation method and application of an epitaxial growth layer and a sodium-sulfur lattice modified lithium-rich manganese-based positive electrode material. By adopting an ethanol wet grinding and coating Na2S method, the first-cycle discharge specific capacity, rate performance and cycle performance are significantly improved, and the voltage attenuation is effectively alleviated.
[0005] CN111082059A discloses a V-doped P2 type sodium ion battery positive electrode material. A V-containing precursor is prepared by a simple sol-gel method, and a high-temperature solid-phase sintering reaction is performed to prepare the V-doped P2 type sodium ion battery positive electrode material.
[0006] Defects of the existing technology: 1. Doping modification starts from the precursor, which requires many process steps, and the precursors of the new material system are yet to be developed; 2. Wet mixing is difficult to evaporate, and some elements precipitate at irregular intervals during the drying process, resulting in problems such as poor consistency; 3. Increasing the upper limit voltage will cause interface problems such as electrolyte decomposition, resulting in increased battery side reactions, severe gas production, and poor consistency.
[0007] Therefore, it is of great significance to develop a method to improve the capacity, cycle stability and rate performance of sodium-ion battery positive electrode materials without increasing the voltage upper limit. Summary of the invention
[0008] In view of the above problems existing in the prior art, the object of the present invention is to provide a sodium ion battery positive electrode material, a preparation method thereof and a sodium ion battery. The positive electrode material of the present invention can improve the capacity, cycle stability and rate performance of the positive electrode material of the sodium ion battery without increasing the voltage upper limit. It can also improve the air stability and processing performance of the material.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a positive electrode material for a sodium ion battery, wherein the positive electrode material for a sodium ion battery is a layered structure, and the positive electrode material for a sodium ion battery is co-doped with a doped metal element and a sulfur element;
[0011] Based on the molar amount of the sodium ion battery positive electrode material, the content of each doping metal element is independently 0.000025 to 0.2, for example, 0.00003, 0.00005, 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., and the total content of the doping metal elements is ≤0.4, for example, 0.4, 0.35, 0.3, 0.2, 0.15, 0.1, 0.08, 0.05 or 0.04, etc.
[0012] Sulfide bond energy is weaker than oxide, S 2- Radius O 2- Large, sulfide micromodification enables the construction of a wider Na + Migrate channel to achieve Na + Different cation doping can regulate the capacity of layered cathode materials in a specific voltage range (generally 2.5-4.0V) and improve the stability of the material structure, keeping the capacity retention rate basically unchanged, and the presence of sulfur can inhibit the O 2- Participation in the electrode reaction process is manifested as an increase in coulombic efficiency.
[0013] During the preparation of positive electrode materials for sodium-ion batteries, due to the loss of Na during the sintering process, it is necessary to maintain a slight excess of Na in the early stage of preparation, and an excess of sodium source (such as sodium carbonate), resulting in residual alkali on the surface of the material such as sodium bicarbonate and sodium hydroxide.
[0014] The present invention adopts co-doping of doped metal elements and sulfur elements, and sulfides are easy to compound with residual alkali, which plays a role in increasing the first cycle charging capacity and stabilizing lattice oxygen to a certain extent during the electrode reaction process. That is, co-doping with sulfides can compensate for the lower first efficiency of the negative electrode when Na is slightly excessive to perform full-electric sodium supplementation. In addition, a slightly excessive amount of cationic dopants can be accumulated on the surface of the material, and after a one-step sintering, an island-shaped coating is formed, further improving the electrode reaction interface.
[0015] The material of the present invention has good air stability and good processing performance, the pH can be reduced to below 12, and the specific surface area is low, which can be as low as 0.3m 2 / g. At the same time, the material of the present invention has a relatively high tap density, which can reach 2.0g / cm 3 .
[0016] In the present invention, pH control is mainly synergistically related to the valence, electronegativity and ionic radius of the doped metal element, and specific surface area control is mainly to achieve a lower specific surface area by adjusting the Na content to reduce residual alkali on the basis of pH control, and the adjustment of the Na content here is mainly related to the doping amount of the S element.
[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0018] Preferably, the metal element includes at least one of Na, Mg, Ni, Ca, B, Al, Zr, Ti, W, Mo, Cr, Sr, Y, Cd, Sn, Sb, Ce, Li, K and Ag, preferably at least one of Li, Ni, Zr and Ti, and more preferably Ni.
[0019] Preferably, based on the molar amount of the sodium ion battery positive electrode material, the content of each doping metal element is independently 0.02 to 0.2, preferably 0.03 to 0.12.
[0020] Preferably, based on the molar amount of the sodium ion battery positive electrode material, the content of sulfur element is 0.00000005-0.05, for example, 0.00000005, 0.0000001, 0.0000005, 0.000001, 0.000005, 0.00001, 0.00005, 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., preferably 0.001-0.02.
[0021] Preferably, the main body of the sodium ion battery positive electrode material is O3 or P2 phase positive electrode material.
[0022] Preferably, the chemical composition of the sodium ion battery positive electrode material is Na x Cu y Fe z Mn a M b O 2+s-nδ S n, wherein 0.6≤x≤1.4, 0≤y≤0.4, 0≤z≤0.5, 0≤a≤0.9, 0.005≤b≤0.4, 0<n≤0.05, -1≤δ≤3, x+2y+3z+3a<4<x+2y+3z+4a, 0.95≤y+z+a+b≤1.05, and M is selected from at least one of Na, Mg, Ni, Ca, B, Al, Zr, Ti, W, Mo, Cr, Sr, Y, Cd, Sn, Sb, Ce, Li, K and Ag.
[0023] wherein x is, for example, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3 or 1.4, y is, for example, 0.05, 0.1, 0.2, 0.3 or 0.4, z is, for example, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, a is, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, b is, for example, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1, 0.2, 0.3 or 0.4, n is, for example, 0.01, 0.02, 0.03, 0.04 or 0.05, and δ is, for example, -1, 0, 1, 2 or 3.
[0024] Preferably, the doping elements need to satisfy that the sum of the other elements except sodium is close to 1.0, and the sum of the total valence is close to 3.0, that is, the total valence of the anion minus the valence of sodium.
[0025] Layered oxide cathode materials can be simplified into compound models, namely Na x TM y TM' z TM” t …O2, whether it is P2 or O3 or other layered oxide structures, must satisfy the requirement that the sum of the corresponding molar numbers of all TM element valences is the total valence of oxygen, that is, 4-x. However, the valence of TM will change during the sintering process, resulting in a deviation between the actual valence state and the theoretical one. In addition, since O is provided by the environment, the sum of the molar ratios of TM needs to be close to 1. For example, Na 0.93 Cu 0.22 Fe 0.37 Mn 0.37 O2 is only the molar ratio of the ingredients, 0.22+0.37+0.37=0.96 (close to 1), 0.93+0.22*2+0.37*3+0.37*4=3.96 (close to 4), and the "close" here means that the positive and negative deviations are less than a certain value, preferably less than or equal to 0.05.
[0026] As a preferred technical solution of the sodium ion battery positive electrode material of the present invention, the surface of the sodium ion battery positive electrode material has a coating.
[0027] Preferably, the coating is distributed on the surface of the sodium ion battery positive electrode material in the form of island distribution.
[0028] Preferably, the coating is formed by making at least one of the raw materials for preparing the positive electrode material of the sodium ion battery excessive.
[0029] In the present invention, the at least one raw material may be a compound of the main element or a compound doped with a metal element, and those skilled in the art may select as needed. For example, the compound of the main element may be at least one of an oxide or carbonate of Cu, Fe, or Mn, and the compound doped with a metal element may be at least one of an oxide, hydroxide, or carbonate of Mg, Ti, Zr, Al, W, Sr, Y, or Ag.
[0030] Preferably, the pH of the sodium ion battery positive electrode material is 11.0-13.0, for example, 11.0, 11.3, 11.5, 11.8, 12.0, 12.1, 12.2, 12.4, 12.6, 12.8 or 13.0, etc., preferably 11.3-12.5, and more preferably 11.5-12.0.
[0031] Preferably, the specific surface area of the sodium ion battery positive electrode material is 0.2 to 1.0 m 2 / g, for example 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g or 1.0m 2 / g, etc., preferably 0.3 to 0.6 m 2 / g.
[0032] Preferably, the BET change value of the sodium ion battery positive electrode material before and after being placed in a constant humidity 50% environment for 30 minutes is preferably -0.03 to 0.1 m 2 / g, for example -0.03m 2 / g, 0.02m 2 / g, -0.01m 2 / g、0m 2 / g, 0.01m 2 / g, 0.03m 2 / g, 0.05m 2 / g, 0.08m 2 / g or 0.1m 2 / g, etc., preferably 0 to 0.05 m2 / g.
[0033] In the present invention, the "BET change value before and after 30 minutes of placement" refers to the specific surface area after placement minus the specific surface area before placement.
[0034] In a second aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described in the first aspect, the method comprising the following steps:
[0035] Mixing raw materials of a sodium ion battery cathode material to obtain a mixed precursor;
[0036] Sintering the mixed precursor to obtain the sodium ion positive electrode material;
[0037] Among them, the raw materials of the sodium ion battery positive electrode material include the main raw materials of the sodium ion battery positive electrode material and the doping raw materials. The main raw materials of the sodium ion battery positive electrode material include a sodium source, and the doping raw materials include a metal element doping source and a sulfur source.
[0038] The method of the present invention starts from the raw materials, adopts metal ions and sulfide ions to co-dope and adjust the material to exert capacity in the same voltage range, has a simple production process, does not require any additional equipment and process, only requires a few groups of materials, and the one-step doping and modification of the material has good consistency. At the same time, in the preparation process of the mixed precursor, by making some raw materials excessive, an island coating can be spontaneously formed, without the need for an additional coating step.
[0039] Preferably, the main raw materials of the sodium ion battery positive electrode material have a slight excess of main elements. Taking Na, Cu, Fe and Mn as the main elements for explanation, the excess of Na element is mainly to make up for the sintering loss. The slight excess of Cu, Fe and Mn can reduce the coating processing steps, and can play a role in consuming residual alkali on the surface, isolating the electrolyte and reducing side reactions, which is beneficial to the processing performance.
[0040] Preferably, the slight excess of the main element is a molar ratio of 0.001 to 0.04, such as 0.001, 0.003, 0.005, 0.007, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035 or 0.04, and preferably 0.003 to 0.02.
[0041] In the present invention, the specific types of the raw materials, metal element doping sources and sulfur sources of the main body of the sodium ion battery positive electrode material are not limited. By way of example and not limitation, the metal element doping source may be at least one of metal oxides, metal sulfides, metal hydroxides and metal salts; the sulfur source may be a metal sulfide.
[0042] It should be noted that the same substance can be used as one or more of the three types of raw materials mentioned above. For example, lithium sulfide can be used as both a metal element doping source and a sulfur source, titanium sulfide can be used as both a metal element doping source and a sulfur source, and sodium sulfide can be used as both a main raw material of the sodium ion battery positive electrode material (specifically a sodium source) and a sulfur source.
[0043] Preferably, based on the mass of the sodium ion battery positive electrode material, the mass fraction of the metal element doping source is 0.005-25%, for example, 0.005%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 13%, 15%, 17%, 18%, 20%, 21%, 22%, 23% or 25%, etc., more preferably 0.1-10%.
[0044] Preferably, based on the mass of the sodium ion battery positive electrode material, the mass fraction of the sulfur source is 0.0001-5%, for example, 0.0001%, 0.0005%, 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 1.5% or 5%, etc., more preferably 0.001-0.5%.
[0045] As a preferred technical solution of the method of the present invention, the sintering atmosphere is an oxygen-containing atmosphere, preferably an air atmosphere or an oxygen atmosphere, and more preferably an air atmosphere.
[0046] Preferably, the sintering temperature is 700-1200°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, etc., preferably 800-1100°C.
[0047] Preferably, the sintering time is 8 h to 36 h, for example, 8 h, 10 h, 12 h, 13 h, 15 h, 17 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 33 h or 36 h, etc., preferably 8 to 24 h, and more preferably 12 h to 20 h.
[0048] Preferably, the heating rate of the sintering is 1 to 10°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, and preferably 2 to 5°C / min.
[0049] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the first aspect.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The present invention can construct a wider range of Na by micro-modification of sulfide + Migrate channel to achieve Na + Different cation doping can regulate the capacity of layered cathode materials in a specific voltage range (generally 2.5-4.0V) and improve the stability of the material structure, keeping the capacity retention rate basically unchanged, and the presence of sulfur can inhibit the O 2- Participation in the electrode reaction process is manifested as an increase in coulombic efficiency.
[0052] At the same time, sulfide co-doping can compensate for the low initial efficiency of the negative electrode when Na is slightly excessive, and perform full-electrolysis sodium supplementation. In addition, a slightly excessive amount of cationic dopants can accumulate on the surface of the material, forming an island coating after a one-step sintering step, further improving the electrode reaction interface.
[0053] (2) The material of the present invention has good air stability and good processing performance, the pH can be reduced to below 12, and the specific surface area is low, which can be as low as 0.3m 2 / g. At the same time, the material of the present invention has a relatively high tap density, which can reach 2.0g / cm 3 .
[0054] (3) The method of the present invention has a simple production process, does not require any additional equipment and process, and only requires a few more groups of materials. Moreover, the one-step doping and modification of the material has good consistency. At the same time, in the preparation process of the mixed precursor, by adding some raw materials in excess, an island coating can be spontaneously formed without the need for an additional coating step. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is the SEM image of material A1;
[0056] Figure 2 is the SEM image of material A2;
[0057] Figure 3 is the SEM image of material A3;
[0058] Figure 4 is the SEM image of material A4;
[0059] Figure 5 is the SEM image of material A5;
[0060] Figure 6 is the SEM image of material B1;
[0061] Figure 7is the SEM image of material B2;
[0062] Figure 8 is the SEM image of material B3;
[0063] Fig. 9 is the SEM image of material B4;
[0064] Fig.10 is the SEM image of material B5;
[0065] Fig.11 is the SEM image of material B6;
[0066] Fig.12 are the XRD patterns of materials A1, A2, A3, A4, A5, B1, B2, B3, B4, B5 and B6. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0068] Comparative Example 1
[0069] Preparation of unmodified Na 0.93 Cu 0.22 Fe 0.37 Mn 0.37 O2:
[0070] Weigh 2.33kg Na2CO3, 0.66kg CuO, 0.98kg Fe2O3 and 1.02kg MnO2, mix and disperse evenly, and then dry to obtain Na 0.93 Cu 0.22 Fe 0.37 Mn 0.37 O2 mixed precursor, and sintered at 960℃ in compressed air atmosphere for 10h, with a heating rate of 3℃ / min, denoted as A1.
[0071] Comparative Example 2
[0072] Preparation of alkali metal-doped Na 0.93 Li 0.04 Cu 0.22 Fe 0.37 Mn 0.37 O2:
[0073] Weigh 2.30kg Na2CO3, 0.069kg Li2CO3, 0.66kg CuO, 0.97kg Fe2O3 and 1.00kg MnO2, mix and disperse evenly, and then dry to obtain Na 0.93 Li 0.04 Cu 0.22 Fe 0.37 Mn0.37 O2 mixed precursor, and sintered at 930℃ in compressed air atmosphere for 16h with a heating rate of 2℃ / min, denoted as A2.
[0074] Comparative Example 3
[0075] Preparation of transition metal-doped Na 1.0 Cu 0.22 Fe 0.37 Mn 0.35 Ni 0.06 O2:
[0076] Weigh 2.37kg Na2CO3, 0.63kg CuO, 0.16kg Ni(OH)2, 0.93kg Fe2O3 and 0.91kg MnO2, mix and disperse evenly, and then dry to obtain Na 1.0 Cu 0.22 Fe 0.37 Mn 0.35 Ni 0.06 O2 mixed precursor, and sintered at 950℃ in compressed air atmosphere for 18h with a heating rate of 5℃ / min, denoted as A3.
[0077] Comparative Example 4
[0078] Preparation of transition metal and alkali metal dual-doped Na 0.93 Li 0.03 Cu 0.22 Fe 0.36 Mn 0.37 Ni 0.02 O2:
[0079] Weigh 2.29kg Na2CO3, 0.052kg Li2CO3, 0.65kg CuO, 0.94kg Fe2O3 and 1.00kg MnO2, mix and disperse evenly, and then dry to obtain Na 0.93 Li 0.03 Cu 0.22 Fe 0.36 Mn 0.37 Ni 0.22 O2 mixed precursor, and sintered at 900℃ in compressed air atmosphere for 12h, with a heating rate of 8℃ / min, denoted as A4.
[0080] Comparative Example 5
[0081] Preparation of sulfur-transition metal dual-doped modified Na 1.02 Cu 0.06 Ni 0.3 Fe 0.33 Mn 0.33 O 1.99 S0.01 :
[0082] Weigh 2.34kg Na2CO3, 0.034kg Na2S, 0.80kg Ni(OH)2, 0.17kg CuO, 0.82kg Fe2O3 and 0.85kg MnO2, mix and disperse evenly, and then dry to obtain Na 1.02 Cu 0.16 Ni 0.2 Fe 0.33 Mn 0.33 O 1.99 S 0.01 The precursors were mixed and sintered at 930°C in a compressed air atmosphere for 15 h with a heating rate of 3°C / min, which was recorded as A5.
[0083] Example 1
[0084] Preparation of sulfur-transition metal dual-doped modified Na 1.02 Cu 0.16 Ni 0.2 Fe 0.33 Mn 0.33 O 1.99 S 0.01 :
[0085] Weigh 2.34kg Na2CO3, 0.034kg Na2S, 0.53kg Ni(OH)2, (0.45=0.40+0.05)kg CuO, 0.82kg Fe2O3 and 0.85kg MnO2, mix and disperse evenly, and then dry to obtain Na 1.02 Cu 0.16 Ni 0.2 Fe 0.33 Mn 0.33 O 1.9 9S 0.01 The precursors were mixed and sintered at 930°C in a compressed air atmosphere for 15 h with a heating rate of 3°C / min, which was recorded as B1.
[0086] In this embodiment, the molar ratio of excess CuO to excess Cu element is 0.02. The copper compound covers the material surface in the form of island distribution.
[0087] Example 2
[0088] Preparation of sulfur-transition metal and alkali metal multi-doped modified Na 0.95 Li 0.04 Cu 0.2 Fe 0.37 Mn 0.37 Ni 0.02 O 1.9 9S 0.01 :
[0089] Weigh 2.32kg Na2CO3, 0.044kg CuS, 0.068kg Li2CO3, 0.55kg Ni(OH)2, 0.56kg CuO, 0.96kg Fe2O3 and 0.99kg MnO2, mix and disperse evenly, then dry to obtain Na 0.95 Li 0.04 Cu 0.2 Fe 0.37 Mn 0.37 Ni 0.02 O 1.9 9S 0.01 The precursors were mixed and sintered at 920°C in a compressed air atmosphere for 20 h with a heating rate of 2°C / min, which was recorded as B2.
[0090] Example 3
[0091] Preparation of sulfur-alkali metal-doped Na 1.0 Li 0.04 Cu 0.22 Fe 0.38 Mn 0.37 O 1.98 S 0.02 :
[0092] Weigh (2.41 = 2.34 + 0.07) kg Na2CO3, 0.021 kg Li2S, 0.64 kg CuO, (0.97 = 0.95 + 0.02) kg Fe2O3 and 0.98 kg MnO2, mix and disperse evenly, and then dry to obtain Na 1.0 Li 0.04 Cu 0.22 Fe 0.38 Mn 0.37 O 1.9 8S 0.02 The precursors were mixed and sintered at 1000°C in a compressed air atmosphere for 16 h with a heating rate of 2°C / min, which was recorded as B3.
[0093] In this embodiment, Na2CO3 and Fe2O3 are in excess, the molar ratio of the excess Na element is 0.03, and the molar ratio of the excess Fe element is 0.01. The Fe compound is distributed in the form of islands and covers the surface of the material.
[0094] Example 4
[0095] Preparation of Sulfur-Transition Metal Doped Modified Na 0.95 Cu 0.3 Fe 0.33 Ti 0.04 Mn 0.33 O 2.0 S0.01 :
[0096] Weigh 2.27kg Na2CO3, 0.011kg TiS3, 0.067kg TiO2, 0.86kg CuO, 0.84kg Fe2O3 and 0.87kg MnO2, mix and disperse evenly, and then dry to obtain Na 0.95 Cu 0.3 Fe 0.33 Ti 0.04 Mn 0.33 O 2.03 S 0.01 The precursors were mixed and sintered at 950°C in an oxygen atmosphere for 18 h with a heating rate of 3°C / min, which was recorded as B4.
[0097] Example 5
[0098] The difference between this embodiment and embodiment 1 is that the content of Ni(OH)2 is adjusted so that the chemical formula of the sulfur-transition metal dual-doped modified sodium ion battery positive electrode material is Na 1.02 Cu 0.26 Ni 0.1 Fe 0.33 Mn 0.33 O 1.99 S 0.01 , denoted as B5.
[0099] Example 6
[0100] Preparation of Sulfur-Transition Metal Doped Modified Na 0.95 Cu 0.3 Fe 0.33 Zr 0.04 Mn 0.33 O 1.98 S 0.02 :
[0101] Weigh 2.27kg Na2CO3, 0.018kg ZrS2, 0.085kg ZrO2, 0.86kg CuO, 0.84kg Fe2O3 and 0.87kg MnO2, mix and disperse evenly, and then dry to obtain Na 0.95 Cu 0.3 Fe 0.33 Zr 0.04 Mn 0.33 O 1.98 S 0.0 The precursors were mixed and sintered at 950°C in an oxygen atmosphere for 18 h with a heating rate of 3°C / min, which was recorded as B6.
[0102] Physical properties:
[0103] pH test: Take the positive electrode material and distilled water in a mass ratio of 1:20, stir magnetically for 10 minutes, let it stand for 5 minutes, measure the pH value and record it as the material pH.
[0104] Tap density test: weigh 50g of positive electrode material into a measuring cylinder, place it in the corresponding position of the tap density tester, vibrate at 80Hz, vibrate 3000 times, read the volume after vibration, repeat three times, 50 / average volume is the tap density.
[0105] BET change value after 30 minutes of placement at 50% constant humidity: Unpack the materials in a dry room with low humidity ≤5%, unpack them in a constant humidity environment of 50% for 30 minutes, then measure BET simultaneously with another unpacked material in a low humidity environment of 20%, and the difference between the two is the change value.
[0106] XRD test: range 10-80 degrees, step size 0.02 degrees, time 0.2, total time 712 seconds.
[0107] SEM test: acceleration voltage 10kV, resolution 10k, general morphology shooting.
[0108] The pH, tap density, BET and BET change value after 50% constant humidity placement for 30 minutes are shown in Table 1.
[0109] Table 1 pH, tap density, and BET test results of materials A1-A4 and B1-B7
[0110]
[0111] The SEM images of the comparison materials show that B1~B6 ( Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 , Fig.11 ) Although there are some fine particles attached to the surface of the particles, the overall surface is relatively clean. Figure 7 The most obvious. A1~A5( Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 ) The particle surface of the material is full of dot-like particles and other fine particles, indicating that the material without S doping modification has undergone a deterioration reaction within the transfer time. Figures 2 to 4 Comparison Figure 1 All showed slight improvement.
[0112] Combination Fig.12The XRD comparison diagrams of A1, A2, A3, A4, A5, B1, B2, B3, B4, B5 and B6 shown in the figure show the characteristic peaks of the layered positive electrode materials (marked with asterisks *). The coordinated doping modification of metal cations and sulfide anions can slightly change the structure of the material to a certain extent, which is mainly manifested in the left and right shifts of the (003) and (104) peaks and the changes in the peak ratio.
[0113] From Table 1, it can be concluded that compared with the materials prepared by the examples of A1-A5 only doped with metal ions and modified with sulfur, the BET and BET change values of the materials co-doped with metal ions and sulfur are significantly reduced, the pH is lower than 12 as a whole, and the tap density is also improved to a certain extent. Therefore, from the perspective of physical property characterization, the modification method of the present invention can achieve the effect of improving the processing performance of the material and improving the air stability.
[0114] In summary, the synergistic doping modification of metal cations and sulfide anions has a more stable crystal structure, a more suitable pH and BET, which in turn can reflect better air stability.
[0115] Battery Assembly:
[0116] The materials of Examples 1 to 6 and Comparative Examples 1 to 5 were respectively used as active materials, mixed in a mass ratio of active material: SP: PVDF of 90:5:5, NMP was added to prepare a viscous glue, coated on aluminum foil, and baked in a vacuum drying oven at 120° C. for 12 h to obtain a positive electrode sheet.
[0117] A 2032 button cell was assembled in an Ar-protected glove box using a sodium metal sheet as the counter electrode, glass fiber (Waterman) as the separator, and 1 mol / L NaPF6EC / DMC=1:1 (Alfa) as the electrolyte.
[0118] Electrochemical performance test:
[0119] The battery was tested in the voltage range of 2.5-4.0V, activated at 0.1C for three weeks, and cycled at 1C for 100 weeks. The discharge capacity at 0.1C in the first week, the discharge capacity retention rate after 100 cycles at 1C, and the average coulombic efficiency in the first three weeks at different rates were recorded. The results are shown in Table 2.
[0120] Table 2 Electrochemical performance test results of materials A1~A5 and materials B1~B6
[0121]
[0122] Table 2, A1-A4 are unmodified, alkali metal doped, transition metal doped and alkali metal-transition metal dual doped, respectively. By co-doping with metal elements (which can be alkali metal elements, such as Li; or transition metals, such as Ni) and sulfur elements, the capacity improvement of doping modification of different types of metal elements is significantly different, and can bring a certain improvement in capacity and cycle retention rate. At the same time, from the perspective of the average coulomb efficiency at different rates, the average coulomb efficiency of transition metal doping at different rates is significantly improved, while the average coulomb efficiency of alkali metal doping is only 0.1C higher.
[0123] As can be seen from Table 1, the introduction of sulfur significantly improves the capacity retention rate of the material and the average coulombic efficiency at different rates, indicating that the presence of sulfur can reduce the side reactions in the electrode reaction process to a certain extent, and is conducive to regulating the capacity within the same voltage range. Therefore, from the perspective of electrochemical performance, the modification method of the present invention can adjust the capacity within a fixed voltage range by doping with different metal ions and S elements, and on this basis improve the consistency and structural stability of the material.
[0124] At the same time, by comparing Example 1 with Comparative Example 5, it can be seen that when the Ni content increases to 0.3, the Ni content is too high and the Cu content is reduced, resulting in extremely poor air stability, the material pH increases from 11.87 to 12.82, and the BET change value after 50% constant humidity placement for 30 minutes shows a nearly exponential growth, resulting in poor material processing performance and difficulty in battery core processing. In addition, the cost will also increase significantly after the increase of Ni. Therefore, excessive metal doping will have an adverse effect on both the material system and the cost.
[0125] By comparing Example 1 with Example 5, it can be seen that reducing the Ni content to 0.1 and adding too much Cu will result in low material capacity and poor cycle performance despite the low pH and small BET change value after 50% constant humidity for 30 min. This may be related to Ni doping. Ni doping can effectively improve the cycle life of the material, and Ni doping can play a certain capacity-enhancing effect. Ni 2+ The electrochemical activity of is slightly higher than that of Cu.
[0126] By comparing Example 2 with Comparative Example 2, it can be seen that the introduction of a small amount of Ni and S co-doping can significantly reduce the BET change value of 50% constant humidity placement for 30 minutes, and the first efficiency, capacity, rate and cycle performance of the electrochemical performance are also relatively excellent.
[0127] By comparing Example 2 and Example 3, it can be seen that increasing Ni doping will lead to an increase in pH, but it can increase the material capacity and cycle performance, which shows the superiority of Ni doping.
[0128] By comparing Example 3 and Comparative Example 2, it can be seen that the introduction of S doping on the basis of increasing the raw materials Na and Fe can form an oxygen / sulfide or sodium oxygen coating layer of Fe, effectively reducing the BET of the material and the BET change value after being placed at 50% constant humidity for 30 minutes, and can improve the cycle performance of the material while ensuring the material capacity and rate performance, indicating that the introduction of S can inhibit the participation of lattice oxygen in the reaction to a certain extent.
[0129] By comparing Example 4 with Example 1, it can be seen that although Ni doping will lead to a higher pH and a larger BET change value after 50% constant humidity placement for 30 minutes, its electrochemical performance is much higher than that of Ti doping, which also illustrates the superiority of Ni doping.
[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0131] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery is a layered structure, and the positive electrode material of the sodium ion battery is co-doped with a doped metal element and a sulfur element; Based on the molar amount of the sodium ion battery positive electrode material, the content of each doping metal element is independently 0.000025~0.2, and the total content of the doping metal elements is ≤0.4; the main metal of the sodium ion battery positive electrode material includes sodium, copper, iron and manganese, and the doping elements of the sodium ion battery positive electrode material include metal elements and sulfur; The chemical composition of the positive electrode material of the sodium ion battery is Na x Cu y Fe z Mn a M b O 2+s-nδ S n , wherein 0.6≤x≤1.4, 0≤y≤0.4, 0≤z≤0.5, 0≤a≤0.9, 0.005≤b≤0.4, 0<n≤0.05, -1≤δ≤3, x+2y+3z+3a<4<x+2y+3z+4a, 0.95≤y+z+a+b≤1.05, and M is selected from at least one of Na, Mg, Ni, Ca, B, Al, Zr, Ti, W, Mo, Cr, Sr, Y, Cd, Sn, Sb, Ce, Li, K and Ag.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The doping metal element is at least one of Li, Ni, Zr and Ti.
3. The sodium ion battery positive electrode material according to claim 2, characterized in that The doping metal element is Ni.
4. The sodium ion battery positive electrode material according to claim 1, characterized in that Based on the molar amount of the sodium ion battery positive electrode material, the content of each doping metal element is independently 0.02-0.
2.
5. The sodium ion battery positive electrode material according to claim 4, characterized in that Based on the molar amount of the sodium ion battery positive electrode material, the content of each doping metal element is independently 0.03-0.
12.
6. The sodium ion battery positive electrode material according to claim 1, characterized in that Based on the molar amount of the sodium ion battery positive electrode material, the content of sulfur element is 0.00000005-0.
05.
7. The sodium ion battery positive electrode material according to claim 6, characterized in that Based on the molar amount of the sodium ion battery positive electrode material, the content of sulfur element is 0.001-0.
02.
8. The sodium ion battery positive electrode material according to claim 1, characterized in that The main body of the sodium ion battery positive electrode material is O3 or P2 phase positive electrode material.
9. The sodium ion battery positive electrode material according to claim 1, characterized in that The surface of the sodium ion battery positive electrode material is coated.
10. The sodium ion battery positive electrode material according to claim 9, characterized in that: The coating is distributed on the surface of the positive electrode material of the sodium ion battery in the form of island distribution.
11. The sodium ion battery positive electrode material according to claim 9, characterized in that: The coating is formed by making at least one of the raw materials for preparing the positive electrode material of the sodium ion battery excessive.
12. The sodium ion battery positive electrode material according to claim 1, characterized in that The pH of the sodium ion battery positive electrode material is 11.0-13.
0.
13. The sodium ion battery positive electrode material according to claim 12, characterized in that: The pH of the sodium ion battery positive electrode material is 11.3-12.
5.
14. The sodium ion battery positive electrode material according to claim 13, characterized in that: The pH of the sodium ion battery positive electrode material is 11.5-12.
0.
15. The sodium ion battery positive electrode material according to claim 1, characterized in that: The specific surface area of the sodium ion battery positive electrode material is 0.2-1.0 m 2 / g.
16. The sodium ion battery positive electrode material according to claim 15, characterized in that: The specific surface area of the sodium ion battery positive electrode material is 0.3-0.6 m 2 / g.
17. The sodium ion battery positive electrode material according to claim 1, characterized in that: The BET change value of the sodium ion battery positive electrode material before and after being placed in a constant humidity environment of 50% for 30 minutes is -0.03~0.1m 2 / g.
18. The sodium ion battery positive electrode material according to claim 17, characterized in that: The BET change value of the sodium ion battery positive electrode material before and after being placed in a constant humidity environment of 50% for 30 minutes is 0~0.05m 2 / g.
19. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 18, characterized in that: The method comprises the following steps: Mixing raw materials of a sodium ion battery cathode material to obtain a mixed precursor; Sintering the mixed precursor to obtain the sodium ion positive electrode material; Among them, the raw materials of the sodium ion battery positive electrode material include the main raw materials of the sodium ion battery positive electrode material and the doping raw materials. The main raw materials of the sodium ion battery positive electrode material include a sodium source, a copper source, an iron source and a manganese source, and the doping raw materials include a metal element doping source and a sulfur source.
20. The method according to claim 19, characterized in that The metal element doping source includes at least one of metal oxides, metal sulfides, metal hydroxides and metal salts.
21. The method according to claim 19, characterized in that The sulfur source is metal sulfide.
22. The method according to claim 19, characterized in that Based on the mass of the sodium ion battery positive electrode material, the mass fraction of the metal element doping source is 0.005-25%.
23. The method according to claim 22, characterized in that Based on the mass of the sodium ion battery positive electrode material, the mass fraction of the metal element doping source is 0.1-10%.
24. The method according to claim 19, characterized in that Based on the mass of the sodium ion battery positive electrode material, the mass fraction of the sulfur source is 0.0001-5%.
25. The method according to claim 24, characterized in that Based on the mass of the sodium ion battery positive electrode material, the mass fraction of the sulfur source is 0.001-0.5%.
26. The method according to claim 19, characterized in that The sintering atmosphere is an oxygen-containing atmosphere.
27. The method according to claim 26, characterized in that The sintering atmosphere is air atmosphere or oxygen atmosphere.
28. The method according to claim 27, characterized in that The sintering atmosphere is air atmosphere.
29. The method according to claim 19, characterized in that The sintering temperature is 700-1200°C.
30. The method according to claim 29, characterized in that The sintering temperature is 800-1100°C.
31. The method according to claim 19, characterized in that The sintering time is 8 to 36 hours.
32. The method according to claim 31, characterized in that The sintering time is 8 to 24 hours.
33. The method according to claim 32, characterized in that The sintering time is 12 to 20 hours.
34. The method according to claim 19, characterized in that The heating rate of the sintering is 1-10°C / min.
35. The method according to claim 34, characterized in that The heating rate of the sintering is 2-5°C / min.
36. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material according to any one of claims 1 to 18.
Citation Information
Patent Citations
V-doped P2 type sodium ion battery positive electrode material and preparation method thereof
CN111082059A
Preparation method and application of epitaxial growth layer and sulfur-sodium lattice modified lithium-rich manganese-based positive electrode material
CN112242510A
A co-doped modified high-nickel ternary material and a preparation method thereof
CN109119628A
Hybrid-phase structure layered oxide material and preparation method and application thereof
CN109585795A